Epidemiology of Measles in Bale Zone, Southeast Ethiopia: Analysis of Surveillance Data from 2013 to 2019 - Tsegaye G; Gezahagn Y; Bedada S; Berhanu N; Gudina G; Mulatu G (Dove Medical Press, 2021)
Geremew Tsegaye,1 Yenealem Gezahagn,2 Shumi Bedada,3 Naod Berhanu,4 Gemechu Gudina,5 Gadisa Mulatu3 1Ethiopian Field Epidemiology and Laboratory Training Program, Faculty of Public Health, Jimma University, Jimma, Ethiopia; 2Department of Epidemiology, Faculty of Public Health, Jimma University, Jimma, Ethiopia; 3Disease Control and Prevention Department, Bale Zone Health Office, Robe, Ethiopia; 4Field Epidemiology, Department of Epidemiology, Faculty of Public Health, Jimma, Ethiopia; 5Public Health Emergency Management Department, Oromia Regional Health Bureau, Addis Ababa, EthiopiaCorrespondence: Geremew Tsegaye Tel +251-92-041-0606Email garamuts0606@gmail.comBackground: Measles remains a cause of vaccine-preventable death in children worldwide. Reported cases in Ethiopiarepresent only a small proportion of expected cases, due to weak measles-based surveillance implementation. In this study, we aimed to analyze 7 years' measles-surveillance data from Bale zone, in order to indicate measles epidemiology and surveillance-related gaps.Methods: This cross-sectional study was conducted from May to June 2019. The study population was all measles cases reported to the Bale Zone Health Office from 2013 to 2019. Data were abstracted from 7 years' measles line lists and case-based reports using a data-abstraction check-list. Data were analyzed using Microsoft Excel and Pivot software, and were presented in tables and graphs.Results: Overall, 4,241 measles cases were reported from 2013 to 2019. Mean age was 7.15 years, and 50.6% were male. The most affected age-group was children < 4 years of age. Analysis indicated that the case-fatality rate was 3.07/1,000 population. Of the total cases reported, 248 (5.8%) were IgM-confirmed. The highest prevalence of 141/100,000 population was reported in 2019. Unvaccinated cases and those with unknown vaccination status numbered 890 (21%) and 731 (17.2%), respectively. The highest number of cases was reported from Ginir and Gololcha districts. Cases increased in autumn each year and peaked in May.Conclusion: Measles is a major cause of morbidity and mortality in Bale, due to poor immunization coverage. Its case fatality is also high, excluding community deaths. Of all the districts included, Ginir reported the highest number of cases. Improving vaccination coverage, early preparedness for the annual epidemic cycle, and strengthening case-based surveillance are important interventions to reduce measles morbidity and mortality.Keywords: Analysis, Bale zone, Ethiopia, Measles, Surveillance